STRATEGIC ROLES OF MAJELIS TAKLIM NURUL HUDA IN STRENGTHENING ISLAMIC RELIGIOUS EDUCATION IN YELLU VILLAGE, SOUTH MISOOL DISTRICT, RAJA AMPAT - Banlol, Siti Sarah; Nurhayati (Pascasarjana IAIN Sorong, 2025)
Majelis Taklim is a non-formal Islamic educational institution that facilitates religious learning and moral development within Indonesia’s Muslim communities. This study investigates the strategic role of Majelis Taklim Nurul Huda in strengthening Islamic religious education among women and youth in Yellu Village, South Misool District, Raja Ampat. Using a qualitative descriptive approach, data were collected through interviews with the chairperson and three members of the Majelis Taklim, two members of the Indonesian Ulama Council (MUI), two mosque committee officers, and two local Islamic community leaders. The findings show that Majelis Taklim Nurul Huda implements integrated pedagogical strategies rooted in Qur’anic literacy, collective religious study, moral exemplification, and youth mentoring. The supporting factors include strong communal solidarity, collective religious identity, and recognition of women as custodians of household spiritual life. However, geographic isolation, limited instructional resources, and low pedagogical capacity among voluntary teachers present challenges. The impact of these strategies is evident in improved religious awareness among families, increased youth participation in mosque-based activities, strengthened ethical conduct, and greater intra-community cooperation. This study contributes to Islamic sociology by showing how non-formal women-led religious institutions in maritime Papua sustain religious identity and moral continuity within geographically marginalized communities.